1978
DOI: 10.1002/ijc.2910210214
|View full text |Cite
|
Sign up to set email alerts
|

Natural cell‐mediated cytotoxicity in rats. III. Effects of immunopharmacologic treatments on natural reactivity and on reactivity augmented by polyinosinic‐polycytidylic acid

Abstract: Treatment of rats with high doses of hydrocortisone, X-irradiation, or cyclophosphamide had a suppressive effect on natural cytotoxicity in vivo. However, when rats were given poly I:C after any of these agents, the levels of NK activity were similar to those in normal rats which had been given poly I:C alone. To explain these findings, we have postulated that a population of pre-NK cells, resistant to hydrocortisone, cyclophosphamide and X-irradiation was induced by poly I:C to become cytotoxic NK cells. Trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
29
3

Year Published

1979
1979
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(38 citation statements)
references
References 35 publications
(9 reference statements)
6
29
3
Order By: Relevance
“…A 6-base DNA motif consisting of an unmethylated CpG dinucleotide flanked by two 5' purines and two 3' pyrimidines was shown to contribute to this response by inducing polyclonal B-cell (3,4,(7)(8)(9)11). Recent work from our laboratory suggested that this B-cell stimulation was mediated by a 6-base nt motif consisting of an unmethylated CpG dinucleotide flanked by two 5' purines and two 3' pyrimidines (12).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A 6-base DNA motif consisting of an unmethylated CpG dinucleotide flanked by two 5' purines and two 3' pyrimidines was shown to contribute to this response by inducing polyclonal B-cell (3,4,(7)(8)(9)11). Recent work from our laboratory suggested that this B-cell stimulation was mediated by a 6-base nt motif consisting of an unmethylated CpG dinucleotide flanked by two 5' purines and two 3' pyrimidines (12).…”
Section: Introductionmentioning
confidence: 99%
“…Yamamoto and others (5)(6)(7)(8)(9) showed that bacterial but not mammalian DNA boosted the lytic activity of natural killer (NK) cells and induced interferon y (IFN-y) production, effects attributed to palindromic sequences present in bacterial DNA (5,10). Other investigators showed that bacterial DNA, especially when complexed to DNA-binding proteins, induced B-cell activation (3,4,(7)(8)(9)11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A role for the macrophage in the regulation of NK activity at a systemic level has been suggested (Oehler & Herberman, 1978) butwhetheranyrelationship exists at the tumour site is unknown. The appearance of various host-cell populations in tumours strongly suggests that the actual events in vivo are dependent upon precisely controlled relationships between the infiltrating cell types.…”
mentioning
confidence: 99%
“…The appearance of various host-cell populations in tumours strongly suggests that the actual events in vivo are dependent upon precisely controlled relationships between the infiltrating cell types. Probably in no situation is this more apparent than the MSV tumour-host system, where the cytolytic activity of both intra-tumour T lymphocytes (fHolden et al, 1976;Gillespie et al, 1977;Plata & Sordat, 1977) and macrophages varies with the growth status of neoplasms. For instance, specifically cytotoxic T cells can be isolated from both regressors and progressors, but in the latter only during the early stages of tumour growth .…”
mentioning
confidence: 99%